Lianas Have a Greater Competitive Effect Than Trees of Similar Biomass on Tropical Canopy Trees - (:unkn) unknown (My University, 2012)
Lianas (woody vines) reduce growth and survival of host trees in both temperate and tropical forests; however, the relative strength of liana-tree competition in comparison to tree-tree competition remains unexplored. When controlling for biomass, lianas may have greater competitive effects than trees because the unique morphology of lianas allows them to reach the forest canopy at relatively small stem diameters and deploy a substantial crown above their host. We tested the hypothesis that lianas have a greater negative effect on canopy trees than do trees of similar biomass with a liana- and tree saplingcutting experiment in a seasonal tropical moist forest in Panama. The response of canopy trees to the cutting treatments was characterized as the change in their daily water use by measuring their sap velocity before and after cutting. We compared the responses of canopy trees around which a similar biomass of either lianas or tree saplings had been cut to control trees with no cutting. Liana cutting increased canopytree sap velocity by ~8% from before to after cutting relative to control trees during the dry season. In contrast, canopy-tree sap velocity did not respond to tree cutting, probably because trees with biomass similar to lianas were confined to the forest understory. We observed a similar pattern of sap velocity changes during the wet season, but treatment differences were not significant. Our results demonstrate that release from liana competition, but not tree competition, resulted in increased water transport in canopy trees, and suggests that relative to their biomass, lianas have greater competitive effects on canopy tree performance than do competing trees.
Keywords: Lianas